(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
The titles "Tilda Fikrda Birlik" and "Jadidlar" are scientific societies being implemented by the state administration of the Republic of Uzbekistan. Their main purpose is to enhance the intellectual potential of the country, promote new ideas and innovations, as well as educate the advanced generation of society. These societies aim to increase spiritual and intellectual development, as well as to provide fair information about social and political issues. The issues of "Knowledge Cultivation and Advanced Generation Education" are dedicated to the spiritual and intellectual development of the younger generation of society. Its main goal is to educate students based on spiritual, knowledge, and ethical values. This aims to support the personal development of students, to make them beneficial members of society, and to contribute to the independence and improvement of the country’s governance.